The Old English verse saints' lives : a study in direct discourse and the iconography of style - Bjork, Robert E., 1949- (McMaster Old English studies and texts, 1985)
Critics have traditionally treated the Old English poems about saints as individual, autonomous works, relating but little to one another except in a broadly generic way. Bjork challenges the traditional view with an examination of the major structural feature that all the poems share: direct discourse. Syntactical and rhetorical analyses of the five poems reveal a consistent use of spech in creating stylistic norms or ideals - stylistic icons - in spiritually perfect figures. In all the poems the speech of the saints in formal, rhetorical, and balanced, the stylistic analogue both of their immutable fith and of the Christ-saint figural connection. The speech of all other characters is measured against this standard; their ability or inability to meet the saintly ideal in language reflects their level of spiritual awareness. The consistency with which these patterns appear sheds new light on the conventions of Old English poetic hagiography.